A meta-analysis of service quality of Iranian university libraries based on the LibQUAL model. Issue 3 (12th November 2018) - Ramezani, Aboozar; Ghazimirsaeed, Seyed Javad; Azadeh, Fereydoon; Bandboni, Mohammad Esmaeilpour; YektaKooshali, Mohammad Hossein
Abstract : Purpose: The purpose of this paper is to assess the quality of Iranian university libraries. Design/methodology/approach: This first systematic review and meta-analysis were based on the PRISMA guidelines by searching in national and international databases from 2003 to January 2017 with standard Persian and English keywords. Data searching, extracting and quality appraising were completed by two researchers, independently. Any unexpected documents were assessed by a third expert researcher. Data were extracted in accordance with the "Strength of the Reporting of Observational Studies in Epidemiology" checklist after the final selection of appraised documents. Random effects size based on Cochrane test and I 2 were used for combining the obtained results from different studies together by considering the heterogeneity of studies. Findings: Based on the meta-analysis conducted in 25 (6.42 percent) included studies, the total sample size was estimated. According to three dimensions of LibQUAL, findings of current information control, affect of service and the library as a place were estimated as 5.37 [CI95%: 5.02, 5.73], 6.91 [CI95%: 5.56, 6.26], and 5.46 percent [CI95%: 5.2, 5.73], respectively. Also, mean of service adequacy and superiority gap are equal to 0.07 [CI95%: −0.22, 0.36] and −2.06 [CI95%: −2.89, −1.23], respectively. There was a significant correlation between three dimensions of service quality and service superiority gap of LibQUAL and geographical regions of Iran ( p <0.01). Also, a significant correlation was found between the gaps of services and three aspects of LibQUAL model and published years through a meta-regression test ( p <0.01). Practical implications: The results obtained from the present study showed that users are relatively satisfied with the quality of services provided by Iranian university libraries. An improvement in the quality of library services can promote the scientific level of universities. Originality/value: The results of the present systematic review and meta-analysis study demonstrate a vital connection between primary research studies and decision-making for policymakers in Iranian university libraries to increase quality services.